Enhancing Antibiotic Efficacy: Exploring Synergistic Interactions between Plant Extracts and Conventional Antibiotics - Donkor, Addai-Mensah; Ahenkorah, Benjamin; Yakubu, Abdallah; Donkor, Martin Ntiamoah (Fine Chemical Engineering, 2024)
Medicinal herbs including Senna alata, Ricinus communis, and Lannea barteri have been utilized for centuries to cure a variety of illnesses caused by microbial infections. This study looked at the synergistic effects of these drugs with traditional antibiotics on clinical isolates of Candida albicans, Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli. The test bacteria were chosen based on their minimal potential for monotherapy and susceptibility to at least one antibiotic with a known genetic basis. The interactions of plant extracts with antibiotics against the chosen pathogenic microorganisms were investigated using the agar well diffusion, broth microdilution, and checkerboard methods. Calculated fractional inhibitory concentration index (FICI) values were used to describe how the extracts and antibiotics interacted. All the extracts from the three plants combined with fluconazole exhibited a synergistic interaction against C. albicans (FICI < 0.5). The minimum inhibitory concentration (MIC) of ampicillin against E. coli was demonstrated to be reduced by the combination of the ethanol extract of S. alata with ampicillin, with a FICI value of 0.4 indicating a synergistic effect. With a synergistic action (FICI ˂ 0.5) against P. aeruginosa, the ethanol extract of S. alata and amoxicillin were successful in reducing the MIC of amoxicillin from 0.32 to 0.17 mg/mL. Aqueous L. barteri extract combined with amoxicillin exhibited synergism (FICI < 0.2) against S. aureus with a reduction of MIC from 0.20 to 0.03 mg/mL. The current study is the first to investigate the aforementioned plants in combination with conventional antibiotics for their antimicrobial activities. The findings of this study could be used to create a useful, applicable, feasible, and alternative source of novel antimicrobial agents.